2019
DOI: 10.1126/science.aay0033
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the RSC complex bound to the nucleosome

Abstract: The RSC complex remodels chromatin structure and regulates gene transcription. We used cryo–electron microscopy to determine the structure of yeast RSC bound to the nucleosome. RSC is delineated into the adenosine triphosphatase motor, the actin-related protein module, and the substrate recruitment module (SRM). RSC binds the nucleosome mainly through the motor, with the auxiliary subunit Sfh1 engaging the H2A-H2B acidic patch to enable nucleosome ejection. SRM is organized into three substrate-binding lobes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 59 publications
10
109
0
Order By: Relevance
“…Fig. 6 RSC SAR complex and does not require a full complement of RSC subunits, as has been proposed 22 . Additionally, previous biochemical analysis has shown that mutation of several basic residues in the N-lobe of Snf2, which lies in close proximity to the exit site DNA, reduces the remodeling rate of the isolated Snf2 enzyme 19 .…”
Section: Rsc Sar Can Break Dna:histone Contacts At the Exit Sitementioning
confidence: 87%
See 4 more Smart Citations
“…Fig. 6 RSC SAR complex and does not require a full complement of RSC subunits, as has been proposed 22 . Additionally, previous biochemical analysis has shown that mutation of several basic residues in the N-lobe of Snf2, which lies in close proximity to the exit site DNA, reduces the remodeling rate of the isolated Snf2 enzyme 19 .…”
Section: Rsc Sar Can Break Dna:histone Contacts At the Exit Sitementioning
confidence: 87%
“…Although this observation may also be due to the individual processing pipelines used in each study or reflect differences between Snf2 and Sth1, mutations in the Snf2 N-lobe near the exit site DNA severely reduce the ability of the isolated enzyme to remodel nucleosomes, supporting the idea that peeling is an intrinsic property of the ATPase domain 19 . Since other RSC subunits have also been shown to interact with the exit site DNA 21,22 , it is likely that multiple components of the full complex act in this process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations